Literature Review: Testing the Quality of Refillable Drinking Water in Community Environments - vildian, luigi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2023)
Water is an inseparable part of all humans. This is because living things cannot live if there is no water, so water is really needed to maintain the continuity of living things. Therefore, this researcher aims to determine the quality of refillable drinking water, whether the product produced meets predetermined quality standards or not. Safe drinking water must meet established standards starting from physical, chemical, microbiological and radioactive aspects in accordance with the Republic of Indonesia Minister of Health Regulation Number 492/MENKES/PER/IV/2010. The results of this research show that 37.5% of DAMIU in Teluk Ambon District, North Balikpapan District meet the effective criteria, namely 66.67% (20) from 30 depots and those that fall within the ineffective criteria are 33.33%. (10) from 30 depots. This indicates that ground water for sanitation and water at the sampling location are generally polluted by coliform bacteria